Symbiosis of the millipede parasitic nematodes Rhigonematoidea and Thelastomatoidea with evolutionary different origins - Seiya Nagae; Kazuki Sato; Tsutomu Tanabe; Koichi Hasegawa (BMC Ecology and Evolution, 2021)
Abstract Background How various host–parasite combinations have been established is an important question in evolutionary biology. We have previously described two nematode species, Rhigonema naylae and Travassosinema claudiae, which are parasites of the xystodesmid millipede Parafontaria laminata in Aichi Prefecture, Japan. Rhigonema naylae belongs to the superfamily Rhigonematoidea, which exclusively consists of parasites of millipedes. T. claudiae belongs to the superfamily Thelastomatoidea, which includes a wide variety of species that parasitize many invertebrates. These nematodes were isolated together with a high prevalence; however, the phylogenetic, evolutionary, and ecological relationships between these two parasitic nematodes and between hosts and parasites are not well known. Results We collected nine species (11 isolates) of xystodesmid millipedes from seven locations in Japan, and found that all species were co-infected with the parasitic nematodes Rhigonematoidea spp. and Thelastomatoidea spp. We found that the infection prevalence and population densities of Rhigonematoidea spp. were higher than those of Thelastomatoidea spp. However, the population densities of Rhigonematoidea spp. were not negatively affected by co-infection with Thelastomatoidea spp., suggesting that these parasites are not competitive. We also found a positive correlation between the prevalence of parasitic nematodes and host body size. In Rhigonematoidea spp., combinations of parasitic nematode groups and host genera seem to be fixed, suggesting the evolution of a more specialized interaction between Rhigonematoidea spp. and their host. On the other hand, host preference of Thelastomatoidea spp. was not specific to any millipede species, indicating a non-intimate interaction between these parasites and their hosts. Conclusions The two nematode superfamilies, Rhigonematoidea and Thelastomatoidea, have phylogenetically distinct origins, and might have acquired xystodesmid millipede parasitism independently. Currently, the two nematodes co-parasitize millipedes without any clear negative impact on each other or the host millipedes. Our study provides an example of balanced complex symbioses among parasitic nematodes and between parasitic nematodes and host millipedes, which have been established over a long evolutionary history.